Sharia Bank Financial Performance: Product And Application Advantages Islamic Values - Munir, Munir (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2023)
This study aims to investigate whether the financial performance of Islamic banks can be improved by product excellence and the implementation of Islamic values. This study has two independent variables: Product Excellence and Application of Islamic Values. In contrast, the dependent variable is Financial Transactions. Quantitative research was employed, and data was collected using questionnaires and interviews. The target population of this study was the customers/users of Bank Muamalat. Primary data was used in this study. A questionnaire was used to collect customer data online via Google Forms. The study results show that product superiority partially has a significant positive impact on customer financial transactions, and the application of Islamic values has a significant positive impact on customer financial transactions at Bank Muamalat Indonesia. These findings suggest that Bank Muamalat should continuously improve and update its products to ensure customer satisfaction in conducting transactions while maintaining the Islamic application system used by Bank Muamalat.